Perancangan Chatbot Berbasis Flowise AI Untuk Layanan Informasi Pada Website Organisasi Kemahasiswaan - Muhammad Hudzaifiy Nur; Pitrasacha Adytia; Kusnandar (Management of Information System Journal, 2026)
The delivery of information on the website of the HIMAPROSI student organization at STMIK Widya Cipta Dharma Samarinda is still one-way, requiring users to open each page individually to find the information they need. This study aims to design and implement a Flowise AI-based chatbot directly integrated into the HIMAPROSI website as a more interactive and efficient information service solution. System development uses the Waterfall method adapted into four stages: data collection, design, implementation, and testing. The chatbot was built using seven components on the Flowise AI platform: PDF File, Character Text Splitter, Jina Embeddings, In-Memory Vector Store, GroqChat (Llama 3.1 8b Instant), Conversational Retrieval QA Chain, and Buffer Memory. This ensures that every response generated is sourced directly from HIMAPROSI’s official documents. Testing was conducted using the Beta Testing method, involving 7 respondents who completed a questionnaire based on a Likert scale. The test results showed an average score of 84%, with the highest score of 89% in the aspects of ease of finding information and speed of obtaining information, proving that the developed chatbot is capable of providing accurate, interactive, and efficient information services for HIMAPROSI website users.